Utilization of Vegetable and Fruit By-products as Functional Ingredient and Food - Lau, Ke Qi; Sabran, Mohd Redzwan; Shafie, Siti Raihanah (Frontiers in Nutrition, 2021)
With the constant growth of the human population, the global demand for food is increasing annually. Food security is an arising issue due to decreased resources and massive waste production from the agricultural sector. For example, not all parts of fruits and vegetables are consumed by consumers, and this phenomenon can lead to huge amounts of food wastes that are produced globally. Moreover, non-utilized agriculture by-products, including seed coat, hull, husk, peels, seeds, and pomace, can cause environmental issues. Hence, efficiently utilizing food wastes, such as vegetable and fruit by-products, could be a way to increase food sustainability, and in line with the United Nations Sustainable Development Goal (SDG) to ensure sustainable consumption and production patterns. Moreover, certain agriculture by-products are reported to have a high nutritional value and could be potentially used as functional ingredient and food in the food industry. This review article summarizes findings on the development of new functional foods by utilizing different types of agriculture by-products, that is, vegetable and fruit by-products as ingredients. Furthermore, the nutritional values, processing methods, product acceptability, and potential uses of these vegetable and fruit by-products are also discussed. These by-products can be an alternative source of nutrients to support the global demand for functional foods and as one of the strategies to cope with food insecurity. Studies have shown that different types of fruit and vegetable by-products were well-incorporated in the development of functional foods, such as bakery products and dairy products. Of great importance, this review article provides an insight of the nutritional value, health benefits, and utilization of fruit and vegetable by-products.